Mechanism of Microbial Metabolite Leupeptin in the Treatment of COVID-19 by Traditional Chinese Medicine Herbs - Lifeng Fu (American Society for Microbiology, 2021)
A TCM formula has played an important role in the treatment of COVID-19 in China. However, the mechanism of TCM action is still unclear.